Cell Death in Liver Disease and Liver Surgery - Christian Stoess; Yeon-Kyung Choi; Janset Onyuru; Helmut Friess; Hal M. Hoffman; Daniel Hartmann; Ariel E. Feldstein (Biomedicines, 2024)
Cell death is crucial for maintaining tissue balance and responding to diseases. However, under pathological conditions, the surge in dying cells results in an overwhelming presence of cell debris and the release of danger signals. In the liver, this gives rise to hepatic inflammation and hepatocellular cell death, which are key factors in various liver diseases caused by viruses, toxins, metabolic issues, or autoimmune factors. Both clinical and in vivo studies strongly affirm that hepatocyte death serves as a catalyst in the progression of liver disease. This advancement is characterized by successive stages of inflammation, fibrosis, and cirrhosis, culminating in a higher risk of tumor development. In this review, we explore pivotal forms of cell death, including apoptosis, pyroptosis, and necroptosis, examining their roles in both acute and chronic liver conditions, including liver cancer. Furthermore, we discuss the significance of cell death in liver surgery and ischemia-reperfusion injury. Our objective is to illuminate the molecular mechanisms governing cell death in liver diseases, as this understanding is crucial for identifying therapeutic opportunities aimed at modulating cell death pathways.